Stem Cell and Idiopathic Pulmonary Fibrosis: Mechanisms and Treatment - Liu, Ming; Ren, Dunqiang; Wu, Dong; Zheng, Jian; Tu, Wenwei (Current Stem Cell Research & Therapy, 2015)
Idiopathic pulmonary fibrosis (IPF) is a progressive and lethal lung disease resulting from multiplex causes. Evidence indicates that stem/progenitor cells might play a key role in IPF pathogenesis and repair, which may provide some novel potential strategies for the future treatment of IPF. In this review, we first summarize the current understanding of the relationship between stem cells and IPF and then review the advancements made in recent clinical trials using stem/progenitor cells, especially mesenchymal stem cells, in treating IPF and their interpretations.
Keywords: Embryonic stem cells